Academic Anxiety Terhadap Skripsi Sebuah Cognitive Distortion Dari Core Belief yang Maladaptif: Integrasi Konseling Cognitive Behavior Therapy dengan Music Therapy - Situmorang, Dominikus David Biondi (Guidance and Counseling Study Program, Pattimura University, 2018)
Thesis is a final project that is quite scary for most students in Indonesia. In the process of compilation, students often do things that are non-productive, such as procrastination and avoid supervisor. Sometimes, excessive academic anxiety of this thesis can lead students to do things beyond common sense, namely suicide. If examined in more depth based on counseling approach Cognitive Behavior Therapy (CBT), academic anxiety to the thesis experienced by students is a cognitive distortion caused by maladaptive core beliefs. Therefore, students who experience it need to get help so that their core beliefs can be more adaptive again. Based on the latest research results, integration of CBT counseling with more modern techniques of music therapy has proved effective in reducing academic anxiety and improving self-efficacy of thesis students. Thus, through this conceptual study, it is hoped that counselors in Indonesia will be able to understand, practice and conduct further research on CBT counseling interventions integrated with music therapy.